Management and Outcomes of Diffuse Large B-cell Lymphoma Post-transplant Lymphoproliferative Disorder in the Era of PET and Rituximab: A Multicenter Study From the Australasian Lymphoma Alliance. Issue 11 (11th November 2021) - Boyle, Stephen; Tobin, Joshua W. D.; Perram, Jacinta; Hamad, Nada; Gullapalli, Veena; Barraclough, Allison; Singaraveloo, Lydia; Han, Min-Hi; Blennerhassett, Richard; Nelson, Niles; Johnston, Anna M.; Talaulikar, Dipti; et al.
Abstract : There are limited data on post-transplant lymphoproliferative disorder (PTLD) in the era of positron emission tomography (PET) and rituximab (R). Furthermore, there is limited data on the risk of graft rejection with modern practices in reduction in immunosuppression (RIS). We studied 91 patients with monomorphic diffuse large B-cell lymphoma PTLD at 11 Australian centers: median age 52 years, diagnosed between 2004 and 2017, median follow-up 4.7 years (range, 0.5–14.5 y). RIS occurred in 88% of patients. For patients initially treated with R-monotherapy, 45% achieved complete remission, rising to 71% with the addition of rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone (R-CHOP) for those not in complete remission. For patients initially treated with R-CHOP, the complete remission rate was 76%. There was no difference in overall survival (OS) between R-monotherapy and R-chemotherapy patients. There was no difference in OS for patients with systemic lymphoma (n = 68) versus central nervous system (CNS) involvement (n = 23) (3-y OS 72% versus 73%; P = 0.78). Treatment-related mortality was 7%. End of treatment PET was prognostic for patients with systemic lymphoma with longer OS in the PET negative group (3-y OS 91% versus 57%; P = 0.01). Graft rejection occurred in 9% (n = 4 biopsy-proven; n = 4 suspected) during the entire follow-up period with no cases of graft loss. RIS and R-based treatments are safe and effective with a low likelihood of graft rejection and high cure rate for patients achieving complete remission with CNS or systemic PTLD.